The challenges that private kindergarten teachers faced in applying distance learning during the corona pandemic in the capital, Amman, and ways to confront them in the future - Al-Suwi, Safaa Husni; Abood, Harith (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the challenges faced by kindergarten teachers in applying distance learning during the Corona pandemic in Amman and ways to confront them from their point of view. They were chosen by the available method, and the results showed that there were challenges faced by kindergarten teachers in their application of distance learning in light of the Corona pandemic, with a total arithmetic average (3.59 out of 5), i.e., to a (significant) degree and at the level of domains; First came the challenges related to the social environment with an average of (3.82), followed by the challenges related to communication in education with an average of (3.68), and thirdly the financial and administrative challenges with an average of (3.60), all of which are at a (large) degree, and finally the technical challenges in the use of distance learning techniques with an average of (3.27) and a degree of (It also showed that the variable years of experience in education did not affect the nature of the challenges faced by kindergarten teachers during distance learning during the Corona pandemic, as the F values ranged between (1.418) and (1.861) for the four axes, which are not statistically significant at the level of (0.05≥α) Based on the results, the researcher recommended the necessity of providing training opportunities for female teachers in the field of educational technology and developing vocational training programs to develop their knowledge on how to face obstacles in applying distance learning tools, and to provide the necessary electronic infrastructure for distance education such as devices, equipment and communication networks, in addition to Suggestions for complementary studies on the topic.
Keywords: Challenges; kindergarten teachers; online education; Corona pandemic